Factors Affecting Activity of Cellulose Enzymes Produced By Three Fungi - Abdel-Rahim, Awad M.; A. Elmustafa, Amina (Gezira Journal of Engineering and Applied Sciences, 2014)
Three fungi (Trichoderma viride, Asperigillus niger and Penicillum digitatum) are used for production of pectinase enzymes. The present study was investigated the effects of some factors on the activities of these pectinase enzyme systems of above three fungi, under laboratory conditions. Two methods (reducing sugar and viscometry) were used for measuring enzymes to the enzyme assay caused a higher increase in ++ and Ca ++, Ba++The addition of Mg activities. f the three fungi. However, less increase was found by the the activity of the pectinase enzyme o +and Hg ++, Cd++. On the other hand, the addition of Ag++and Mn ++, Zn++, Fe++addition of Cucaused a decrease in the activity of this enzyme. The activity of the pectinase enzymes produced was increasing with increasing temperature with the maximum at . digitatumPand iger A. n by. It was Cο 50was highly active at temperature T. viride enzyme of . However, the pectinaseCο40found that the maximum activity of the pectinase enzymes produced by A. niger was at pH 9. While the filtrates of both T. viride and P. digitatum showed two peaks at pH 6 and pH 9.